Slice-selective Adiabatic Magnetization T(2)-PreparAtion (SAMPA) for Efficient T(2)-Weighted Imaging at Ultra-High Field Strengths - Dyvorne, Hadrien (Magn Reson Med, 2015)
PURPOSE: At high field, T(2)-weighted (T(2)w) imaging is limited by transmit field inhomogeneity and increased radiofrequency power deposition. In this work we introduce SAMPA (Slice-selective Adiabatic Magnetization T(2) PrepAration) and demonstrate its use for efficient brain T(2)w imaging at 7T. METHODS: SAMPA was designed by subsampling an optimized B(1) insensitive rotation (BIR4) waveform with small tip angle linear subpulses. In order to perform T(2)w imaging, SAMPA was inserted before a fast gradient echo acquisition. The off-resonance behavior, B(1) robustness and slice selectivity of the novel T(2) preparation module were analyzed using Bloch simulations. The performance of SAMPA for T(2)w imaging was demonstrated in phantom experiments as well as in the brains of healthy volunteers at 7T. RESULTS: Based on simulations, the proposed design operates at peak B(1) of 15 μT and higher, within a 400 Hz bandwidth. T(2) values were in strong agreement with spin echo-based T(2) mapping in phantom experiments. Whole brain, interleaved multislab 3D imaging could be acquired with 0.8 mm(3) isotropic resolution in 5:36 min per T(2) weighting. CONCLUSION: Compared with previous adiabatic T(2) preparation techniques, SAMPA allows for slice-selectivity, which can lead to efficient and robust acquisitions for T(2)w imaging at high field.